Adaptasi New Normal Tourism Dalam Meningkatkan Perekonomian Masyarakat Di Sekitar Waduk Cengklik - Nurul Anggita; Muhammad Jolang Umar Mucthar; Siti Hadiyati Nur Hafida (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
The Covid-19 pandemic has caused a significant decline in tourism activity and has had an impact on the economy. With the new normal concept, the government reopens tourism activities by implementing strict health procedures. The purpose of this study was to determine the economic adaptation of small traders during the new normal period, as well as the community's response to the development of tourism in the Cengklik Reservoir during the new normal, and to describe the adaptation of the community around the Cengklik Reservoir to small traders. Cengklik Reservoir tourism development and analysis of Cengklik Reservoir tourism in order to be able to support increasing the income of the surrounding community. This research is a quantitative research using a survey approach. Respondents in this study amounted to 30 small traders. The data collection technique was carried out directly by using a survey questionnaire. After the data collection process, the researcher conducted an analysis using descriptive statistical analysis. The results showed that during the Covid-19 pandemic, the economy of small traders around the Cengklik Reservoir tourist area, Ngemplak District, experienced a decline. Therefore, efforts need to be made to mobilize resources to develop the economic potential of the community in order to increase community productivity, so that human resources and natural resources around the community can be developed and utilized. The results showed that during the Covid-19 pandemic, the economy of small traders around the Cengklik Reservoir tourist area, Ngemplak District, experienced a decline. Therefore, efforts need to be made to mobilize resources to develop the economic potential of the community in order to increase community productivity, so that human resources and natural resources around the community can be developed and utilized. The results showed that during the Covid-19 pandemic, the economy of small traders around the Cengklik Reservoir tourist area, Ngemplak District, experienced a decline. Therefore, efforts need to be made to mobilize resources to develop the economic potential of the community in order to increase community productivity, so that human resources and natural resources around the community can be developed and utilized